Norms, culture and local infrastructure: Evidence from a decentralised economy - Sarmistha Pal (Institute for the Study of Labor (IZA), 2010)
Culture as reflected in social and religious norms may be pivotal to social organization in a decentralised economy where local authorities are responsible for the provision of local public goods. We distinguish between individualist and collectivist cultures to argue that collectivist culture may promote rules to indulge in family, social and religious values at the cost of individual values promoting material objects and may thus result in inefficient choice of pubic goods. We use Indonesia as a case in point to classify communities strictly adhering to traditional adat laws and Islamic religion as promoting collectivist culture. Results using 1997 and 2007 Indonesian Family Life Survey community-level panel data highlight that, even after controlling for other variables, traditional collectivist communities strongly adhering to adat and Islam tend to have significantly greater access to social (rather than physical) infrastructural goods; similar pattern is reflected in the allocation of community spending to these goods.
Keywords: D02; H41; O43; P51; 330; decentralization; collectivist culture; adat law; Islam; social and physical infrastructure; allocation of spending; community development; Indonesia